The psychiatrist and his patient - Mazza, Salvatore; Azzoni, Antonella (Medicina e Morale, 1986)
Among the medical sciences that, all of them, require particular commitment and dedication from those who practise them, psychiatry can undoubtedly be considered the science that, more than any other, burdens the bearer of it with human and social responsibility.